Directors remuneration and firm performance among distressed firms - Abdullah, Shamsul Nahar (Emerald, 2006)
The purpose of this study is to investigate the extent to which firm's performance, the structure of the board of directors and ownership determine directors' remuneration in Malaysia among distressed firms. The study uses publicly available data from a sample of 86 distressed firms and 86 matched non-distressed firms for 2001 financial year. The findings for the full sample show that directors' remuneration is not associated with firm's profitability, as measured by ROA. A negative and significant association is observed between directors' remuneration and lagged ROA. With regard to corporate governance, board independence and the extent of non-executive directors' interests are found to have negative influence on directors' remuneration. In addition, findings also reveal that directors' remuneration is positively associated with firm's growth and size. In sub-sample analyes, a strong negative relation is observed between ROA and directors' remuneration for healthy sub-sample.